2021
DOI: 10.31729/jnma.6251
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus in Nepal

Abstract: Staphylococcus aureus is both a frequent commensal and a leading cause of endocarditis, bacteremia, osteomyelitis and skin and soft tissue infections and device-related infections. We performed this minireview to summarize the prevalence of Staphylococcus aureus among clinical samples and estimate the proportion of methicillin-resistant Staphylococcus aureus. The prevalence of Staphylococcus aureus among clinical isolates in Nepal is 34.5%. On average, the proportion of multi-drug resistance in Staphylococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…18,19 As compared to previous studies, infections with MRSA is in increasing trend in our country. [6][7][8] We found prevalence of MRSA to be 31.2% in our study. This must be due to unregulated use of antibiotics in our setting which shows necessity for prompt implementation of antimicrobial resistance (AMR) policies in hospitals, and implementation of AMR act by Government of Nepal to contain AMR; including MRSA in our context.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…18,19 As compared to previous studies, infections with MRSA is in increasing trend in our country. [6][7][8] We found prevalence of MRSA to be 31.2% in our study. This must be due to unregulated use of antibiotics in our setting which shows necessity for prompt implementation of antimicrobial resistance (AMR) policies in hospitals, and implementation of AMR act by Government of Nepal to contain AMR; including MRSA in our context.…”
Section: Discussionsupporting
confidence: 56%
“…According to previous findings, vancomycin seems as good treatment option against MRSA related infections. [6][7][8] Routine AST report using modified Kirby Bauer's disc diffusion method for reporting resistance to vancomycin is not recommended and should be confirmed by phenotypic dilution technique. 14 We performed agar dilution method for determining minimum inhibitory concentration (MIC) of vancomycin and found that, no MRSA isolate was resistant to it (MIC ≤ 2 mcg/ml for all MRSA isolates).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria often develop resistance to βlactam antibiotics by synthesizing βlactamase, an enzyme that attacks the βlactam ring (Shrestha et al, 2021).To overcome this resistance, β-lactam antibiotics are often administered alongside β-lactamase inhibitors e.g amoxicillin (β lactam antibiotic) and clavulanic acid (βlactamase inhibitor). The clavulanic acid is designed to overwhelm all βlactamase enzymes, bind irreversibly to them, and effectively serve as an antagonist so that the amoxicillin is not affected by the βlactamase enzymes (Luthra et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The US Centre for Disease Control reports that S. aureus , just behind Escherichia coli , is the second most prevalent pathogenic bacteria. Methicillin-resistant S. aureus (MRSA) has been considered to be a leading pathogen closely relevant to human beings, firstly identified as hospital associated (HA-MRSA), then community associated (CA-MRSA) ( Xu et al, 2011 ; Deng et al, 2015b ; Shrestha et al, 2019 , 2021 ). In the recent decade, however, a large number of studies have reported MRSA in animals, and subsequently in animal meat and raw food samples.…”
Section: Introductionmentioning
confidence: 99%